2016
DOI: 10.1111/inm.12246
|View full text |Cite
|
Sign up to set email alerts
|

Improving the physical health of people with severe mental illness in a low secure forensic unit: An uncontrolled evaluation study of staff training and physical health care plans

Abstract: The life expectancy of people with severe mental illnesses is substantially reduced, and monitoring and screening for physical health problems is a key part of addressing this health inequality. Inpatient admission presents a window of opportunity for this health‐care activity. The present study was conducted in a forensic mental health unit in England. A personal physical health plan incorporating clearly‐presented and easily‐understood values and targets for health status in different domains was developed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 36 publications
4
52
1
Order By: Relevance
“…Nine studies examined various factors related to ART use. Three out of four studies found no evidence of a difference in ART use between people living with SMI and HIV and those living with HIV alone [23,9 | P a g e 29,45]. The exception to this was a small study carried out in Italy (n=27) which found that those with new-onset psychosis were less likely to be using ART than those with HIV only [46].…”
Section: Hiv-related Factorsmentioning
confidence: 94%
See 3 more Smart Citations
“…Nine studies examined various factors related to ART use. Three out of four studies found no evidence of a difference in ART use between people living with SMI and HIV and those living with HIV alone [23,9 | P a g e 29,45]. The exception to this was a small study carried out in Italy (n=27) which found that those with new-onset psychosis were less likely to be using ART than those with HIV only [46].…”
Section: Hiv-related Factorsmentioning
confidence: 94%
“…Some of the same barriers apply to adherence to medication for both conditions: alcohol and substance use; side effects; lack of social support; difficulties accessing treatment; transportation; resources to buy medication; patient experience of the health services including relationships with staff [6,8]. Although people with SMI have much higher rates of death from 4 | P a g e suicide and other unnatural causes, the vast majority of excess mortality is due to those conditions which are the most common cause of death among the general population [9,10]. Similarly, although AIDS-related causes account for around a third of deaths among people living with HIV/AIDS [11], PLHA are at higher risk of non-communicable diseases (NCDs) such as cancers, liver disease and cardiovascular disease which account for 40% of deaths [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 80% of nurse respondents reported they would like further training on the management of diabetes, cardiovascular health, and nutrition. This barrier was noted by nearly 90% of mental health staff in a more recent UK M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 study with in-patients indicating that despite staff training, additional support is perceived necessary in order to facilitate uptake of personalised health care plans (Haddad, Llewellyn-Jones, Yarnold & Simpson, 2016).…”
Section: Introductionmentioning
confidence: 99%